2017
DOI: 10.1016/j.ajog.2017.06.029
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based recommendation to increase the dosing frequency of buprenorphine during pregnancy

Abstract: Background Dose-adjusted plasma concentrations of buprenorphine are significantly decreased during pregnancy compared to the non-pregnant state. This observation suggests that pregnant women may need a higher dose of buprenorphine than non-pregnant individuals in order to maintain similar drug exposure (plasma concentrations over time after a dose). The current dosing recommendations for buprenorphine during pregnancy address the total daily dose of buprenorphine to be administered but the frequency of dosing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 16 publications
0
33
0
1
Order By: Relevance
“…The model predictions are in agreement with the current clinical practice in pregnant women. At the Pregnancy Recovery Center at Magee‐Womens Hospital, among 62 pregnant women followed up in an opioid agonist treatment programme, 68% of the patients chose a three or four times dosing per day to maximally suppress craving/withdrawal symptoms .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model predictions are in agreement with the current clinical practice in pregnant women. At the Pregnancy Recovery Center at Magee‐Womens Hospital, among 62 pregnant women followed up in an opioid agonist treatment programme, 68% of the patients chose a three or four times dosing per day to maximally suppress craving/withdrawal symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated in a small cohort of pregnant women that plasma concentrations of BUP and the corresponding BUP exposure is significantly reduced during pregnancy compared to the postpartum state [19]. We have suggested that more frequent dosing of buprenorphine will reduce the time that treated women are likely to be subtherapeutic during pregnancy [19,20]. Our observations may at least in part explain the report of Jones et al [21], who in a large clinical trial reported higher study withdrawal rates in subjects assigned to BUP compared with methadone.…”
Section: Introductionmentioning
confidence: 99%
“…Volume of distribution and increased clearance during pregnancy compared to the postnatal period, causes even 50% reduction of the drug's concentration, frequently to subtherapeutic dose levels [44]. The latest pharmacokinetic studies suggest that apart from the need to increase the daily buprenorphine dosage, its frequency also needs to be increased to three-four times per day [45]. Buprenorphine was confirmed as a substitution therapy drug later than methadone and there are fewer reports on its influence on pregnant women Wyniki szeregu badań dotyczących relacji między dawkami metadonu stosowanymi w późnym okresie ciąży a częstością występowania i nasileniem NAS nie doprowadziły do ustalenia jednoznacznych wniosków.…”
Section: Buprenorphine Substitution Therapymentioning
confidence: 99%
“…Objętość dystrybucji i zwiększenie klirensu podczas ciąży, w porównaniu z okresem poporodowym, powodują nawet 50-procentową redukcję stężenia leku, często do dawek subterapeutycznych [44]. Ostatnie badania farmakokinetyczne sugerują, oprócz potrzeby zwiększenia dziennej dawki buprenorfiny, zwiększenie częstotliwości dawkowania trzy do czterech razy dziennie [45]. Buprenorfina została zatwierdzona do terapii substytucyjnej później niż metadon i dlatego jest mniej doniesień na temat jej wpływu na kobiety w ciąży i ich potomstwo.…”
Section: Terapia Substytucyjna Buprenorfinąunclassified
“…Relative to methadone, BUP-SL offers the advantages of lower NOWS severity in infants [9] and greater convenience for pregnant women by removing the requirement of near-daily clinic visits for dosing [10]. BUP-SL limitations include risk for diversion [11], potential for non-adherence [11], poor retention [12][13][14], and daily peak-trough effects [15], with evidence that BUP-maintained pregnant women may be at sub-therapeutic doses for most of their dosing interval [16].…”
Section: Introductionmentioning
confidence: 99%